The Concept of Love of Country in 19th-Century Painting - Utari, Shela Dwi; Hudiyanto, Reza; Wahyudi, Deny Yudo (Yupa: Historical Studies Journal, 2024)
Love for the country does not only focus on the physical resistance carried out at that time but can also take other forms. In this case, painting artists realized their love for their homeland through visual aspects. This research explores the forms of the concept of love for the country in Indonesian painting, especially in the 19th century. This research uses the historical method with five stages: topic selection, heuristics, source criticism, interpretation, and historiography. The result of this research is that paintings in the 19th century illustrate the concept of patriotism as seen from the objects depicted. The object of the painting is not only fixated on the role and power of the colonial nation but also gives the impression that the Indonesian nation also has a role. This can be seen from some of Raden Saleh's paintings such as Daendels' potert, the painting Between Life and Death, and the painting of Prince Diponegoro's arrest, which gives the meaning that Indonesians also played a role in historical events that occurred at that time.